2011
DOI: 10.1007/s11999-010-1487-1
|View full text |Cite
|
Sign up to set email alerts
|

The John Charnley Award: Risk Factors for Cup Malpositioning: Quality Improvement Through a Joint Registry at a Tertiary Hospital

Abstract: Background Few studies have examined factors that affect acetabular cup positioning. Since cup positioning has been linked to dislocation and increased bearing surface wear, these factors affecting cup position are important considerations. Question/purposes We determined the percent of optimally positioned acetabular cups and whether patient and surgical factors affected acetabular component position. Methods We obtained postoperative AP pelvis and crosstable lateral radiographs on 2061 consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
425
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 500 publications
(459 citation statements)
references
References 48 publications
23
425
2
9
Order By: Relevance
“…This is consistent with a recent report in the literature that shows a much higher variability in cup position than previously reported [5]. Two patients required early revision in our series and one patient sustained an intraoperative fracture.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent report in the literature that shows a much higher variability in cup position than previously reported [5]. Two patients required early revision in our series and one patient sustained an intraoperative fracture.…”
Section: Discussionsupporting
confidence: 93%
“…A reduced risk of dislocation with increased risk of aseptic revision was observed in the anterolateral transgluteal approach as compared with the posterior approach with a specific implant type [32]. The authors attributed this to possible acetabular cup malpositioning (inclination angle of greater than 50°), which was more common with the anterolateral approach [9].…”
Section: Discussionmentioning
confidence: 99%
“…29 (6) 29 (6) 30 (6) 290 (6) 28 (5) 29 (6) Number ( 8002 (19) 758 (18) 77 (12) 6438 (20) 63 (3) 666 (17) \ 0.001 32 14,418 (34) 1485 (35) 201 (30) 11,034 (35) 423 (23) 1275 (32) 36 15,441 (36) 1502 (36) 264 (40) 11,119 (35) 1166 (63) 1390 (35) [ 36 3882 (9) 412 (10) 112 (17) 2678 (8) 159 (9) 521 (13) Missing 695 (2) 69 (2) 13 (2) 478 (2) 40 (2) 95 (2) BMI = body mass index; ASA = American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the prevalence of 'optimal' acetabular cup positioning in primary THA in a tertiary teaching hospital was reported to be 49 % [6]. The study reported that surgical approach, surgeon case numbers and obesity independently predicted malpositioned cups.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that surgical approach, surgeon case numbers and obesity independently predicted malpositioned cups. While there are a number of papers describing clinical results of acetabular revision with large bone defect [7,8], there is paucity of data regarding cup position in the setting of revision THA [6]. The purpose of this study was to evaluate the cup position in the setting of revision THA for Paprosky type III acetabular defect using the Martell digital image analysis technique.…”
Section: Introductionmentioning
confidence: 99%